2018
DOI: 10.19045/bspab.2018.700152
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Macrophomina phaseolina isolates prevailing in Sindh, Pakistan

Abstract: Macrophomina phaseolina (Tassi) Goid is economically important fungal pathogen with wide host range. In this study we found morphological and phenotypical variation among isolates of the fungus infecting sunflower crop in Sindh province of Pakistan. Thirty two M. phaseolina isolates were obtained from infected plant samples of sunflower collected from different ten districts viz.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The morphological and cultural studies revealed that M. phaseolina isolates were grouped into different categories based on growth pattern (appressed, fluffy, and velvety), growth rate, colony color (light grey, grey, and black), aerial mycelium (present and absent), sclerotial initiation time, sclerotial number (less, moderate, and high), sclerotia size (small, medium, and large) and sclerotia shape (round, ovoid, and irregular). Similarly, earlier studies reported that the M. phaseolina associated with different crops also grouped the isolates into different categories based on diameter growth on medium, colony color, mycelial characteristics, the morphology of the sclerotia, and sclerotial initiation time ( Suriachandraselvan and Seetharaman, 2003 ; Sharma et al., 2004 ; Gupta et al., 2012 ; Sharma et al., 2012 ; Tanaji et al., 2017 ; Wagan et al., 2018 ; Thirunarayanan et al., 2020 ; Chiranjeevi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The morphological and cultural studies revealed that M. phaseolina isolates were grouped into different categories based on growth pattern (appressed, fluffy, and velvety), growth rate, colony color (light grey, grey, and black), aerial mycelium (present and absent), sclerotial initiation time, sclerotial number (less, moderate, and high), sclerotia size (small, medium, and large) and sclerotia shape (round, ovoid, and irregular). Similarly, earlier studies reported that the M. phaseolina associated with different crops also grouped the isolates into different categories based on diameter growth on medium, colony color, mycelial characteristics, the morphology of the sclerotia, and sclerotial initiation time ( Suriachandraselvan and Seetharaman, 2003 ; Sharma et al., 2004 ; Gupta et al., 2012 ; Sharma et al., 2012 ; Tanaji et al., 2017 ; Wagan et al., 2018 ; Thirunarayanan et al., 2020 ; Chiranjeevi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 76%
“…the morphology of the sclerotia, and sclerotial initiation time (Suriachandraselvan and Seetharaman, 2003;Sharma et al, 2004;Gupta et al, 2012;Sharma et al, 2012;Tanaji et al, 2017;Wagan et al, 2018;Thirunarayanan et al, 2020;Chiranjeevi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%